Tinjauan Yuridis Penerapan Sistem Kerja pada Bank Permodalan Nasional Madani (PNM) Mekaar Perspektif Omnibus Law Cipta Kerja - Maghfirah firah (CV Rewang Rencang, 2025)
Abstract The research was conducted empirically with a juridical-sociological approach to the implementation of employment relations in the field. The results show a discrepancy between employment practices and the provisions of the Job Creation Law, especially regarding the status of employment relations and protection of workers' rights. The conclusion states that the implementation of the work system at PNM Mekaar needs adjustments to be in line with applicable employment regulations within the framework of the Omnibus Law.